Paradigm Shifts in Strategic Culture of Pakistan: An Assessment of Traditional versus Non-traditional Threat Perceptions - Ghazanfar, Bilal; Khalid, Iram; Shareh Qazi, Muhammad (Annals of Human and Social Sciences, 2022)
This study aims to establish a causal relationship that how nontraditional security challenges does not necessarily qualify to acquire a high-priority position in strategic decision-making of Pakistan owing to entanglement with traditional security concerns. The study examines that continual focus on traditional security issues has induced ‘tunnel vision trap’ where Pakistan cannot transit or at least reprioritize traditional national security challenges with non-traditional security concerns by applying securitization theory. The study finds out that even after displaying responsibility and caution in how it approaches strategic red lines within and beyond its region, its high prioritization of traditional threat perceptions weighs down on its internal nontraditional security concern. The research concludes that for Pakistan, even transitioning from geostrategic prioritization of national interest to the pursuit of geoeconomic objectives does not divorce its traditional security priority in decision-making. Such a tethered securitization architecture renders all transitionary junctions to its strategic culture futile or inconsequential.